Assessment on The Impact of Distributed Generation (Renewable Energy) Penetration to The National Grid Protection System Performances using ERACS Software - Ali, Adlan; Norddin, Nurbahirah; Rusli, Nur Alia (International Journal of Integrated Engineering, 2019)
This paper is an assessment on the impact of distributed generation penetration to the national grid protection system performance based on a model simulated using software named ERACS. In recent years, the need and demand of using renewable energy as power source has increased greatly. This demand then led to the integration of distributed generation on the grid. Distributed generation has a lot of advantages. It can act as emergency supply, offering high quality power as well as reducing the carbon emission. However, it also has advantages that cause major concern, with protection being a major concern. Two models are used to simulate different scenario, focusing on protection blinding impact to the overcurrent relay used that is Inverse Definite Time Relay using ERACS. The results of the simulation are then studied in order to determine the relay performance during normal condition and when injected with renewable energy.